HUBUNGAN PENGETAHUAN TENTANG SIKAP ERGONOMI DENGAN GANGGUAN MUSCULOSKELETAL PADA PERAWAT - Utami, Ressa Andriyani; Setyaningsih, Tri; Hemawayanti, Heni (Jurnal Kesehatan Holistic, 2017)
The high mobility of labor and lack of knowledge about the science of ergonomics at high risk of causing musculoskeletal disorders in nurses. The purpose of this study was to investigate the relationship between knowledge of ergonomic attitude with musculoskeletal disorders in nurses Room Surgery, Emergency Installation, ICU, and ICCU Husada Hospital Jakarta. This research uses descriptive correlative research design. The sample of this research is 83 people. The results showed p-value 0.001 means there is a relationship between knowledge of ergonomic attitudes with musculoskeletal disorders in nurses. It is expected that the nurses of the Surgical Room, Emergency Installation, ICU, and ICCU can improve their knowledge of ergonomics so as to create high quality of work and life, decrease of morbidity due to work and accidents and create a sense of comfort in work.